2009
DOI: 10.1007/s10995-009-0477-y
|View full text |Cite
|
Sign up to set email alerts
|

Family Income Gradients in the Health and Health Care Access of US Children

Abstract: This study sought to examine the shape and magnitude of family income gradients in US children’s health, access to care, and use of services. We analyzed cross-sectional data from the 2003 National Survey of Children’s Health, a telephone survey of 102,353 parents of children aged 0–17 years. Associations between family income [Below 100% Federal Poverty Level (FPL), 100–199% FPL, 200–299% FPL, 300–399% FPL, 400% FPL or Greater] and a set of 32 health and health care indicators were examined using linear polyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
112
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(131 citation statements)
references
References 50 publications
12
112
0
1
Order By: Relevance
“…Research has confirmed this finding with recent studies demonstrating that poverty, and the unmet basic needs that result from it, results in greater susceptibility to disease and poorer health across the life span. [3][4][5][6]23,[28][29][30][31][32][33][34][36][37][38] Despite numerous leaders in the field advocating for addressing social needs as part of primary care [9][10][11][12]39 and professional guidelines emphasizing the need to address social determinants, [13][14][15][16][17] there has been little evidence to help guide this practice. 27,40 A previous study by our group demonstrated that a similar system can lead to more discussion and referrals for family psychosocial problems by pediatric trainees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has confirmed this finding with recent studies demonstrating that poverty, and the unmet basic needs that result from it, results in greater susceptibility to disease and poorer health across the life span. [3][4][5][6]23,[28][29][30][31][32][33][34][36][37][38] Despite numerous leaders in the field advocating for addressing social needs as part of primary care [9][10][11][12]39 and professional guidelines emphasizing the need to address social determinants, [13][14][15][16][17] there has been little evidence to help guide this practice. 27,40 A previous study by our group demonstrated that a similar system can lead to more discussion and referrals for family psychosocial problems by pediatric trainees.…”
Section: Discussionmentioning
confidence: 99%
“…2 Children raised in poverty experience poorer health than children from more advantaged backgrounds and commonly face unmet basic needs such as food security, stable housing, or an adequately heated home. [3][4][5][6][7][8] For decades, leaders in the field of pediatrics have argued that addressing a child's social needs falls within the purview of the child health provider. [9][10][11][12] Numerous American Academy of Pediatrics policy statements and Bright Futures health supervision guidelines support this view and have been published in an effort to reinforce this practice.…”
Section: What This Study Addsmentioning
confidence: 99%
“…It is evident that there is a strong gradient effect of social risk factors on child well-being; as social risk factors increase in number, so does the risk for poor mental health. 14,15 This gradient is also seen specifically in the following relationship between family income and child health; increases in family income are associated with a corresponding increase in child physical health, behavioral health, development, and health care access and utilization. 14 Thus, children from families across the spectrum of lower income levels incur some risk for adverse health outcomes, with children from families facing the greatest poverty experiencing the greatest risk.…”
Section: Poverty and Compromised Mental Healthmentioning
confidence: 95%
“…Although some health problems emanate from genetic vulnerabilities or random exposures or events, childhood health is also a function of parental SES (18). Rates of many childhood illnesses (e.g., asthma, ear infections, injury, respiratory infections, conduct problems) increase as family SES decreases (4,19), and effects of parental SES can be seen early in life. Children of low-SES parents are more likely to be born prematurely and to have low birth weight, even after adjusting for covariates (20,21).…”
Section: Causality and Its Discontentsmentioning
confidence: 99%